Pemberian Nugget Tempe terhadap Kadar Hemoglobin pada Remaja Putri - Nurhidayah, Nurhidayah (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2020)
In Indonesia, 23.9 percent of adolescent girls suffer from anemia. Adolescent girls with anemia have poor memory and are less thorough in scholastic exams, resulting in inferior learning achievements. They are also more susceptible to illness, putting them at risk when they become pregnant. The goal of this study was to see how providing tempeh nuggets affected adolescent girls' hemoglobin levels at SMP Negeri in Gorontalo City. This sort of study uses a pre-experimental design with a pretestposttest research design with a single group design and a sample of 43 persons drawn by chance. Provision of tempe nuggets was the independent variable, whereas hemoglobin levels in teenage girls was the dependent variable. The average value or difference in the average hemoglobin levels of adolescent girls after being fed tempeh nuggets was 0.40 gr/dl, standard deviation was 0.42, and sig (2-tailed) = 0.000< 0.05, according to the findings of statistical test analysis with Paired T-test. Conclusion At SMP Negeri Gorontalo City, giving tempeh nuggets has an effect on hemoglobin levels in adolescent girls.